EFFECTIVENESS TEST OF BLACK CUMIN SEEDS (NIGELLA SATIVA) EXTRACT ON THE GROWTH OF KLEBSIELLA PNEUMONIAE AND PSEUDOMONAS AERUGINOSA BACTERIA - Nadya Nazimuddin Putri; Linda Chiuman; Chrismis Novalinda Ginting; Ermi Girsang (Universitas Medan Area, 2021)
Black cumin seeds are known to have beneficial contents as antibacterial. This study aimed to determine the effectiveness of black cumin seed extract (Nigella sativa) on the growth of Klebsiella pneumoniae and Pseudomonas aeruginosa. The method used was the disc diffusion method. The ethanol extract of black cumin seeds gain by maceration method and was made into various concentration (5, 7.5, 10, 12.5, and 15)%. For positive control, ciprofloxacin disc were used and negative control used distilled water. The research model used was in vitro experimental research. The results showed that ethanol extract of black cumin seeds have antibacterial activity against Klebsiella pneumoniae with inhibition zone diameters (4.5, 6.7, 10.1, 11, 12.8) mm, Pseudomonas aeruginosa with inhibition zone diameters (7.5, 12, 12.6, 13.4, 15.6) mm, positive controls respectively (24.3 and 20.7) mm and negative controls (0). It can be concluded that black cumin seed extract has an inhibiting effect on the growth of Klebsiella pneumoniae and Pseudomonas aeruginosa.